Plano de Projeto: Projeto do Assador Churrasco Grego - Trindade, Cristiano da (Universidade do Vale do Rio dos Sinos, 2018)
This work aims to analyze how to develop and design a Barbecue Grill for Greek, for launch and sale in the national market in the year 2018, with an estimated cost of manufacturing of R$ 400.00. Beginning in the second half of 2017 and scheduled for completion in june 2018, this product will be developed and designed by the company Anodilar Utilidades Domésticas, in Caxias do Sul – RS. This work uses the Project Management Knowledge Guide (PMBOK) as a basis for good project management practices, with respect to the management of: integration, scope, time, cost, quality, human resources, communication, risks, acquisitions and stakeholders.
Keywords: Projeto; Gerenciamento de Projeto; Plano de Gerenciamento de Projeto; Process; Project Management; Plan of Project Management